Resistance inductors for potato late blight management in Peru - Sanabria, K.; Pérez, W.; Sánchez, D.; Andrade-Piedra, J.L. (International Potato Center, 2018)
The effectiveness and efficiency of commercial resistance inductors (RIs) for LB control in the central highlands of Peru were studied. Susceptible plants of cv. Yungay were sprayed with PKplus®, Manvert Biolet®, Miconic® and Manvert Silikon®, and then they were inoculated with a complex P. infestans isolate under laboratory and greenhouse conditions. PKplus® and Manvert Biolet® were the most effective in disease control. Both products were selected for field trials and were applied on four potato cultivars with different levels of susceptibility in three locations during the rainy season. Treatments were PKplus®, Manvert Biolet®; and propineb (alone or alternated); a Decision Support System (DSS, using systemic and/or contact fungicides); and a plot without fungicides. Relative area under the disease progress curve (RAUDPC), yield, environmental impact (EI) and marginal rate of return (MRR) were registered in all experiments. The most effective (low RAUDPC, high yield and low EI) and efficient (MRR > 50%) treatments were PKplus® and propineb alone, PKplus® alternated with propineb and the DSS in susceptible cultivars; PKplus® and Manvert Biolet® alternated with propineb, and propineb alone in a moderately resistant cultivar; and propineb alone in a resistant cultivar. These results showed that it´s possible to control potato LB in a profitable and environmentally-friendly manner, even in susceptible cultivars during the rainy season